PENGARUH PENERAPAN LKPD BERBASIS INKUIRI TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROKARBON - Iryani, Auliyah Maulana Putra, (Menara Ilmu, 2019)
This research aims to reveal the effect of applying LKPD based on guidedinquiry on student learning outcomes on hydrocarbon material in class XI MIPA at SMAN1 Ranah Pesisir. This type of research is quasi-experimental research using the designof Non-Equivalent Control Group Design. This research was conducted at SMAN 1 RanahPesisir. The research subjects were selected using purposive sampling technique in whichclass XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class. Theresearch instrument used was a test of learning outcomes in the form of multiple choicequestions. The average posttests value in this experimental class students was 80,7 ishigher than the control class with an average value of 71,9. The research data wasanalyzed using SPSS series 16.00. Based on data analysis shows that the sample class isnormally distributed and homogeneous so that t-test can be carried out, the significancevalue is obtained (sig) 0.000 <0.005 then the decision rejects Ho. This means that theexperimental class learning outcomes are higher than the control class significantly. Theconclusion of this study shows that the use of guided inquiry-based LKPD on hydrocabonematerial significantly influences the learning outcomes of class XI students in SMAN 1Ranah Pesisir.Keywords :LKPD, guided inquiry, learning outcomes , hydrocarbons